Caracterização química e potencial carrapaticida de óleos essenciais de Eucalyptus spp. Frente a Rhipicephalus microplus - Paulucio, Vanderson de Ataide (2021)
Rhipicephalus microplus, a bovine parasite of worldwide relevance, is responsible for economic losses in cattle farming. Its control has encountered barriers such as the development of populations resistant to conventional ticks. In this scenario, studies of alternatives to control R. microplus are increasingly relevant, especially plant-based ticks. The present study aimed to study the chemical diversity and evaluation of the tick activity of the essential oil (EO) of eight species of Eucalyptus spp. on R. microplus larvae. The study of chemical diversity was carried out by means of Gas Chromatography coupled with Mass Spectrometry (GC-MS) and Nuclear Magnetic Resonance (NMR). In the in vitro assay, the EOs were evaluated in the larval pack test (LPT) with six repetitions in each treatment and negative control being distilled water and 3% Tween 80® (m v-1 ). Through the chemical similarity analysis it was possible to observe two distinct groups in which, for the two evaluated techniques (CG-MS and NMR), the species E. smithii (ESM) and E. urophylla x E. camaldulensis (EURC) were included on the same group, demonstrating to be significantly different from all other species evaluated. However, they did not show similarities in relation to the tick activity. The α-pinene and 1,8-cineole components were identified as the compounds that discriminated these two species from the others. In the biological assay, the species E. grandis (EGR), E. tereticornis (ETI) and E. urophylla x E. grandis (EURG) showed the highest mortality values at the lowest concentration tested, with 99% mortality of larvae at the concentration of 1.25% (mv-1 ). EGR was the species that presented the lowest values of CL50 (0.38% m v-1 ) and CL90 (0.78% m v-1 ). Through multivariate analysis it was possible to suggest that the components α-pinene and γ-terpinene would be related to the tick activity, providing information for the development of alternative products for the control of R. microplus.